But that's not right, is it Miss? Colonization and conscientious objection through drama. Issue 2 (1st December 2019) - Anderson, Elizabeth; Bellamy, Marsha; Douglas, Nikki
AbstractThis article presents an account of a short research project in which two primary school teachers and the researcher collaborated to design drama work to help their students navigate challenging journeys. A short case study of practice over four to six months, it was documented and considered reflectively in order for the practice to be of use to other teachers. From safe New Zealand classrooms, the two teachers, one with Year 6 students, the other with Year 8, used drama to look at the tyranny of colonization and at resistance by conscientious objection. The research followed a case study process over four to six months, in two schools. The two teachers in this study let their students imagine colonization and resistance, and helped them see with new eyes. The students were challenged to question different perspectives on right and wrong and to navigate their own direction with critical thought and empathy. In the class that explored the rights of others in another age through literature heightened their awareness and responsibility for their own work, and in turn deepened their responses to ideas. In the other class, while colonization had been the original commendable theme, the students made their own connections to their own lives and community, and revealed a degree of perception and insight that holds promise for the way those students will participate and balance their responsibilities as citizens.